Evaluasi Kinerja Cooler #1533 Pada Unit Distilasi #1500 PT. X - Ayu, Dinda Laras; Wahyuningtyas, Aulia (universitas teuku umar, 2025)
PT. X is a company that produces the first Hydrogen Peroxide (H2O2) in Indonesia. The raw materials used in producing hydrogen peroxide (H2O2) at PT X are hydrogen (H2), oxygen (O2), water (H₂O) and supporting raw materials, namely WS (working solution), catalyst, stabilizer and ethylene. In the process of making hydrogen peroxide there are many stages in order to get the results on demand. This certainly requires supporting tools in the process such as coolers. The special task carried out is “Evaluation of Cooler #1533 Performance at Distillation Unit #1500 PT. X. Based on the calculation, the Rd value and %heat efficiency for 5 days tend to fluctuate. The Rd value ranges from 0.00094832 btu/hr.ft2.ᵒF to 0.002121257 btu/hr.ft2 .ᵒF, while the heat efficiency value ranges from 48% to 51%. The HE evaluation results on the 31st have the highest Rd value of 0.00212157 btu/hr.ft2 .ᵒF) so that the resulting heat efficiency value is 50%. While the HE evaluation results on the 28th have the lowest Rd value of 0.00094832 (btu/hr.ft2.ᵒF) so that it has the highest efficiency of 51%. The overall head coefficient (Uc) value is greater than the design overall coefficient (Ud) which indicates that the heat transfer in a clean state is higher than in a dirty state, so it can be said that cooler #1533 is still in a state worth using. The ΔP value for the shell has a value of 0.086605283 Psi and the ΔP value on the tube is 0.007 Psi range. This value is still below the standard value allowed, which is 10 Psi.